Effects of computerized cognitive training for children with dyslexia: An ERP study. (August 2020) - Lotfi, Salahadin; Rostami, Reza; Shokoohi-Yekta, Mohsen; Ward, Richard T.; Motamed-Yeganeh, Negin; Mathew, Abel S.; Lee, Han-Joo
Abstract: This feasibility study investigated the effects of adaptive computerized cognitive training on visual-spatial working memory (VSWM), and reading performance in children with dyslexia. Children were assigned into a VSWM training group that received a 5-week ( 30 h) computerized adaptive training program focusing on VSWM, or a waitlist control group. Behavioral and ERP measures of VSWM-related indices and reading ability were taken at baseline, post-training/waiting, and 6-month follow-up to evaluate the effects of training. Results revealed the training group demonstrated significant behavioral improvements at post-training and at a 6-month follow-up in visual attention (IVA-CPT), response control (visual Oddball tasks), and VSWM (WMTB-C & visual 1-back tasks), compared to the control group. Although the training group did not show significant improvements in reading abilities at post-training, the improvement was significant at the follow-up assessment. In addition, relative to the control group, we observed greater P3b amplitudes on the visual 1-back task for the training group at post-training with a large effect. These preliminary findings suggest that an intensive cognitive training can serve as a potentially effective standalone or adjunctive training to improve cognitive control and reading abilities of children with dyslexia. Highlights: We implemented a computerized cognitive training targeting visual-spatial working memory for children with dyslexia. The training group demonstrated substantial behavioral improvements at post-training and at a 6-month follow-up. We observed greater P3b ERP amplitudes on the visual 1-back task for the training group at post-test.